2017
DOI: 10.9758/cpn.2017.15.3.261
|View full text |Cite
|
Sign up to set email alerts
|

The Korean Version of the University of California San Diego Performance-based Skills Assessment: Reliability and Validity

Abstract: ObjectiveThe study’s aim was to develop and standardize a Korean version of the University of California San Diego Performance-based Skills Assessment (K-UPSA), which is used to evaluate the daily living function of patients with schizophrenia.MethodsStudy participants were 78 patients with schizophrenia and 27 demographically matched healthy controls. We evaluated the clinical states and cognitive functions to verify K-UPSA’s reliability and validity. For clinical states, the Positive and Negative Syndrome Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These include the financial domain (ability to count money, make changes, and pay bills), the communication domain (ability to understand specific situations, using telephones and letters, and to properly express oneself), the comprehension/planning domain (ability to understand newspaper article content and to know what one needs), the transportation domain (ability to use public transportation and consider transfers and calculate time, among others), and the household skills domain (ability to select food in preparation for cooking). In this study, the Korean version of the UPSA was used ( Kim et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…These include the financial domain (ability to count money, make changes, and pay bills), the communication domain (ability to understand specific situations, using telephones and letters, and to properly express oneself), the comprehension/planning domain (ability to understand newspaper article content and to know what one needs), the transportation domain (ability to use public transportation and consider transfers and calculate time, among others), and the household skills domain (ability to select food in preparation for cooking). In this study, the Korean version of the UPSA was used ( Kim et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Korean version of the Connor-Davidson Resilience Scale (K-CD-RISC), a brief self-rating questionnaire for measuring resilience, was also administered to evaluate resilience among participants and shows great internal consistency (Cronbach's α = 0.93) [40,41]. In the general population of 577 people, the mean CD-RISC was 80.4 (standard deviation [SD] = 12.8) and the median value was 82.3 (73, 90) [42].…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…Higher scores indicate higher resilience and are negatively correlated with anxiety and depression. We used the Korean version of the BRS validated by Kim et al [39]. In this study, the BRS showed good internal consistency, with a Cronbach's alpha of 0.791.…”
Section: Brief Resilience Scalementioning
confidence: 99%